Letter - Lewis, J.
032-0024-001 11 Ash Rd Aldershot Dear Sir I thank you for your letter explaining the attitude of Communists, re Russia & Finland. It has enlightened me I sincerely agree that aggression is altogether wrong, & never mind from whence it comes. Knowing that the Labor cause is purely democratic & for justice, I am please to be able to send a little help either to be forwarded to the Finns, or Spanish, as you think good. Being just a working man, I am anxious the little I may give should go in the right direction. Hence my letter of inquiry. Yrs faithfully J Lewis To Mr Tewson Assistant Secretary 292/946/32/24